Albumin level and progression of coronary artery lesions in Kawasaki disease: A retrospective cohort study - Xia, Yuhan; Qiu, Huixian; Wen, Zhengwang; Shi, Hongying; Yu, Huan; Li, Jie; Zhang, Qihao; Wang, Jianjie; Rong, Xing; Wu, Rongzhou; Chu, Maoping (Frontiers in Pediatrics, 2022)
Background: Albumin (ALB) level is closely associated with the occurrence of intravenous immunoglobulin (IVIG) resistance and coronary artery lesions (CALs) in Kawasaki disease (KD). But little is known about the association between ALB level and CALs progression, which is critical to the prognosis of KD patients. This study aims to investigate the effect of the ALB level on CALs progression in KD patients. Methods: 3479 KD patients from January 1, 2005, to November 30, 2020, in Wenzhou, China were recruited. A total of 408 KD patients who had CALs and ALB data, and finish the follow-up as requested were enrolled in this study. They were classified into the low ALB group and the normal ALB group, divided by 30 g/L. CALs outcomes were classified into two categories according to the CALs changes from the time that CALs were detected within 48 hours before or after IVIG treatment to one month after disease onset: progressed and no progressed. Multiple logistic regression models were used to assess the independent effect of ALB level on CALs progression among KD patients. Stratified analysis was performed to verify the ALB level on CALs progression among patients in different subgroups. Results: Higher proportion of IVIG resistance (P<0.001), receiving non-standard therapy (P <0.001), and receiving delayed IVIG treatment (P=0.020) were detected in patients with lower ALB level. Patients with lower ALB level had higher C-reactive protein (CRP) level (P=0.097) and White blood cell count (WBC) (P=0.036). After adjustment for confounders, patients with lower ALB level had higher odds of CALs progression; the adjusted odds ratio (OR) was 3.89 (95% CI: 1.68,9.02). Similar results were found using stratification analysis and sensitivity analysis. Male gender and age over 36 months, as covariates in multiple logistic regression models, were also associated with CALs progression. Conclusions: Low ALB level is identified as an independent risk factor for CALs progression in KD patients. Male gender and age over 36 months are also proved to be risk factors for CALs progression. Further investments are required to explore its mechanisms.